ISLAMIC ENTREPRENEURIAL ORIENTATION AND BUSINESS SUSTAINABILITY IN PESANTREN-BASED ENTERPRISES - Anila Dani Sakinah (PAPUA: International Journal of Sharia Business Management, 2026)
This study explores the role of Islamic Entrepreneurial Orientation (IEO) in enhancing Business Sustainability within Pesantren-Based Enterprises through a qualitative case study approach. Islamic Entrepreneurial Orientation is conceptualized as the integration of entrepreneurial dimensions, including innovativeness, proactiveness, and risk-taking, with Islamic values such as amanah (trustworthiness), ‘adl (justice), sidq (honesty), and accountability to Allah. Data were collected through in-depth interviews, observations, and document analysis involving pesantren leaders, business managers, employees, and relevant stakeholders. The findings reveal that Islamic Entrepreneurial Orientation significantly contributes to business sustainability by strengthening organizational resilience, stakeholder trust, ethical business practices, and long-term competitiveness. Furthermore, the study demonstrates that sustainability in pesantren-based enterprises encompasses economic, social, organizational, environmental, and spiritual dimensions. The integration of entrepreneurial capabilities with Islamic ethical principles enables pesantren enterprises to achieve sustainable growth while maintaining their educational mission, religious identity, and contribution to community welfare. The study highlights the strategic importance of Islamic entrepreneurship as a model for sustainable and inclusive business development.